The Impact of COVID-19 Lockdown on Cases of and Deaths From AIDS, Gonorrhea, Syphilis, Hepatitis B, and Hepatitis C: Interrupted Time Series Analysis - Xinsheng Wu; Xinyi Zhou; Yuanyi Chen; Ke Zhai; Ruoyao Sun; Ganfeng Luo; Yi-Fan Lin; Yuwei Li; Chongguang Yang; Huachun Zou (JMIR Publications, 2023)
BackgroundChina implemented a nationwide lockdown to contain COVID-19 from an early stage. Previous studies of the impact of COVID-19 on sexually transmitted diseases (STDs) and diseases caused by blood-borne viruses (BBVs) in China have yielded widely disparate results, and studies on deaths attributable to STDs and BBVs are scarce. ObjectiveWe aimed to elucidate the impact of COVID-19 lockdown on cases, deaths, and case-fatality ratios of STDs and BBVs. MethodsWe extracted monthly data on cases and deaths for AIDS, gonorrhea, syphilis, hepatitis B, and hepatitis C between January 2015 and December 2021 from the notifiable disease reporting database on the official website of the National Health Commission of China. We used descriptive statistics to summarize the number of cases and deaths and calculated incidence and case-fatality ratios before and after the implementation of a nationwide lockdown (in January 2020). We used negative binominal segmented regression models to estimate the immediate and long-term impacts of lockdown on cases, deaths, and case-fatality ratios in January 2020 and December 2021, respectively. ResultsA total of 14,800,330 cases of and 127,030 deaths from AIDS, gonorrhea, syphilis, hepatitis B, and hepatitis C were reported from January 2015 to December 2021, with an incidence of 149.11/100,000 before lockdown and 151.41/100,000 after lockdown and a case-fatality ratio of 8.21/1000 before lockdown and 9.50/1000 after lockdown. The negative binominal model showed significant decreases in January 2020 in AIDS cases (-23.4%; incidence rate ratio [IRR] 0.766, 95% CI 0.626-0.939) and deaths (-23.9%; IRR 0.761, 95% CI 0.647-0.896), gonorrhea cases (-34.3%; IRR 0.657, 95% CI 0.524-0.823), syphilis cases (-15.4%; IRR 0.846, 95% CI 0.763-0.937), hepatitis B cases (-17.5%; IRR 0.825, 95% CI 0.726-0.937), and hepatitis C cases (-19.6%; IRR 0.804, 95% CI 0.693-0.933). Gonorrhea, syphilis, and hepatitis C showed small increases in the number of deaths and case-fatality ratios in January 2020. By December 2021, the cases, deaths, and case-fatality ratios for each disease had either reached or remained below expected levels. ConclusionsCOVID-19 lockdown may have contributed to fewer reported cases of AIDS, gonorrhea, syphilis, hepatitis B, and hepatitis C and more reported deaths and case-fatality ratios of gonorrhea, syphilis, and hepatitis C in China.